Disturbances of functional condition of pro-oxidant and antioxidant systems in guinea pigs’ lungs in experimental allergic alveolitis - Baida, Mariana Ljubomurivna (Journal of Education, Health and Sport, 2017)
We have analyzed the results of experimental work of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde) and antioxidant (superoxide dismutase, catalase) systems in guinea pigs’ lungs in experimental allergic alveolitis. The results of investigation showed that a significant increase in conjugated diene level in animals’ lungs was observed at all stages of experimental allergic alveolitis development under the conditions of immobilization stress as compared with control group, indicating activation of this marker. The same changes occurred with malondialdehyde content, indicating excessive accumulation of this lipid peroxidation product in lung tissue. Oxygen-derived free radicals produced by phagocytes are believed to contribute to lung tissue damage. A lung defence mechanism against oxidative stress produces antioxidant molecules. In the early period of experiment (24th, 34th days) compensatory increasing superoxide dismutase and catalase in the lungs of guinea pigs has been reported. Late period of this pathology (44 th, 54 th days) was accompanied with reduction of these antioxidant enzymes. Increased oxidant levels and decreased antioxidant defences can contribute to the progression of experimental allergic alveolitis.